Growth, carbon assimilation and quality of kesum (Persicaria minor) as exposed to zinc oxide nanoparticles - Zainuren, Noor Fatehah; Ibrahim, Mohd Hafiz; Che Abdullah, Che Azurahanim; Tuan Syaripah Najihah (Sciencedomain International, 2019)
Aims: This study was conducted to investigate the effect of zinc oxide nanoparticles towards the Persicaria minor that can be used as a guidance for further toxicity investigation of ZnO-NPs. Study Design: A Completely Randomized Block Design (RCBD) was used with three replication. Each unit was consisted with eight plants and the total of 96 plants were used in this study. Place and Duration of Study: This study was conducted in plot 1, Vegetables Field plot for Teaching and Research, Taman Pertanian Universiti, Universiti Putra Malaysia (UPM) Selangor, Malaysia, from May 2018 until August 2018. Methodology: Persicaria minor were exposed to four different concentration of zinc oxide nanoparticles (ZnO-NPs) which were (50,100 and 150 mg/L) and 0 mg/L as a control. The ZnO-NPs was dissolved in distilled water before being applied to plants. 40 mL of ZnO-NPs solution was applied to each plant. The growth, carbon assimilation and also secondary metabolites were measured in this experiment. Results: The results showed that the treatment of zinc oxide nanoparticles enhanced growth of the Persicaria minor as the plant treated with zinc oxide nanoparticles had higher plant height and total biomass when compared to control treatment. However, the analysis revealed that the treatment of zinc oxide nanoparticles highly and significantly influenced the carbon assimilation and quality of this plant as the treated plants showed reduction in chlorophyll content, photosynthesis rate, stomatal conductance and transpiration rate but increased in production of secondary metabolites. The increased in production of plant secondary metabolites may be attributed by the plant protection mechanism due to metabolic stress caused by high concentration of zinc oxide nanoparticles. Conclusion: This research will progressively help in contributing some reliable and valid data on the effect of zinc oxide nanoparticles (ZnO-NPs), towards the Persicaria minor that can be used as guidance for further experimental investigation regarding this field.